(2^4*3^3:54+7^2)-4^2=(16*27:54+49):3-16=(432:54+49):3-16=(8+49):3-16=57:3-16=19+16=35
(2^5+19):3-5^2*3^3:45=(32+19):3-25*9:45=51:3-225:45=17-5=12
11^2-(5^3-6^2*3^3:9^2)=121-(125-36*9:81)=121-(125-324:81)=121-(125-4)=121-121=0
2^5*7^2:56-(10^2-79)=32*49:56-(100-79)=1568:56-21=28-21=7
(2^4*3^3:54+7^2)-4^2=(16*27:54+49):3-16=(432:54+49):3-16=(8+49):3-16=57:3-16=19+16=35
(2^5+19):3-5^2*3^3:45=(32+19):3-25*9:45=51:3-225:45=17-5=12
11^2-(5^3-6^2*3^3:9^2)=121-(125-36*9:81)=121-(125-324:81)=121-(125-4)=121-121=0
2^5*7^2:56-(10^2-79)=32*49:56-(100-79)=1568:56-21=28-21=7